Actividad reproductiva de los erizos Lytechinus variegatus y Echinometra lucunter (Echinodermata: Echinoidea) en relación con factores ambientales en el Golfo de Cariaco, Venezuela - Espinoza G., R. A.; Reyes, J. L.; Himmelman, J. H.; Lodeiros, C. (Revista de Biología Tropical, 2008)
Reproductive activity of the sea urchins Lytechinus variegates and Echinometra lucunter (Echinodermata: Echinoidea) in relation to environmental factors at the Gulf of Cariaco, Venezuela. We made monthly determinations of gonad development, female:male ratio, and reproductive index (gonad weight as a percentage of total wet weight) of Lytechinus variegatus and Echinometra lucunter during 16 months at Turpialito in the Gulf of Cariaco, Venezuela. The cover of macroalgae and sea grasses in the collection sites was recorded monthly, water temperature was monitored continuously, and salinity, oxygen content and seston concentration were recorded at weekly intervals. For both sea urchin species, there was high variability in the gonad index throughout the study and the male to female ratio was 1:1. The gonad index of L. variegatus tended to be higher from July to November, and there was a high percentage of spawning (phases IV, V) individuals during most of the year. For E. lucunter the gonad index did not show a clear pattern and individuals with immature gonads were observed throughout the study. There was no clear relationship between reproductive events and the environmental factors studied for either L. variegatus or E. lucunter, although, for L. variegatus, gametogenesis may have been related to low temperature and gonad maturation with high temperatures. Rev. Biol. Trop. 56 (Suppl. 3): 341-350. Epub 2009 January 05.